Estudo da variabilidade de custos em orçamentos de obras residenciais utilizando o método de Monte Carlo - Monteiro, Agatha Martins (2020)
In the middle of the transformations of the world industry, with advances in information technologies, software for calculations and projects, improvements in the quality control of materials, etc., we see that the Brazilian construction industry still executes processes of the last century. In the planning of costs and budget of works, there were also no changes. Analysts use spreadsheet editors to assemble their compositions, prepare their surveys, quotations, assemble unit price compositions without worrying too much about the quality of that information. In civil construction, it is not common to return work to the budget and planning team, whether or not what is being budgeted is meeting the work. This work aims to understand and update the knowledge on calculating the variability of costs in budgets by means of graphs of Monte Carlo simulation in costs of residential works of economic standard in Greater São Paulo, through the methodology of a case study a work in a construction company. Presenting in the results, analysis of the spreadsheets comparing the results of the simulations x actual realized values of the work, thus being able to verify the variability of costs and the validation of the Monte Carlo method as a tool for analyzing risks and uncertainties for decision making regarding of construction costs.